SEMANTICAL DIFFERENCES OF VERB PHRASEOLOGISMS IN THE TRILOGY "KARAKALPAK DASTANY (KARAKALPAK EPIC)" BY T.KAYIPBERGENOV - Tanirbergenov Jenisbay Utepbergenovich; Atabaev Khudaibergen Medetbaevich (Western European Studies, 2024)
In the study of the semantics of phraseology in linguistics, the principles of their division into semantic groups, classification, various methods are specially studied. Although the issue of semantics of phraseology in Karakalpak linguistics was discussed in some works, no special research was done. The meanings of the phraseologies are wide and varied. Such phraseologies have a special role in conveying the ideas, stories, images and characters, actions, mental states, and inner feelings of the characters in an artistic and effective way. This article explores the semantic differences of the verb phraseologisms used in the noveltrilogy "Karakalpak Dastany" by the people's writer of Uzbekistan and Karakalpakstan T.Kaipbergenov. It identifies the semantic differences of the phraseology, which expresses the mental states and inner feelings of a person, such as joy, delight, enjoy, calmness, anger, suffering, remorse, encouragement, fear. The use of such lexemes such as soul, eyes, eyelids, head, mouth, face, mind, heart, lungs, liver, blood, soul, and breast, their function in expressing positive and negative inner feelings of a person is proved by examples.
Keywords: phraseologism; verb phraseologisms; semantics; negative feeling